A influência do esqueleto açúcar-fostato no transporte da molécula de DNA - Sarmento, Ricardo Gondim (2008)
This dissertation analyses the influence of sugar-phosphate structure in the electronic transport in the double stretch DNA molecule, with the sequence of the base pairs modeled by two types of quasi-periodic sequences: Rudin-Shapiro and Fibonacci. For the sequences, the density of state was calculated and it was compared with the density of state of a piece of human DNA Ch22. After, the electronic transmittance was investigated. In both situations, the Hamiltonians are different. On the analysis of density of state, it was employed the Dyson equation. On the transmittance, the time independent Schrödinger equation was used. In both cases, the tight-binding model was applied. The density of states obtained through Rudin-Shapiro sequence reveal to be similar to the density of state for the Ch22. And for transmittance only until the fifth generation of the Fibonacci sequence was acquired. We have considered long range correlations in both transport mechanism